THE MAIN DIRECTIONS OF COMMODITY POLICY AT DOMESTIC ENTERPRISES IN AN INNOVATIVE ECONOMY (Neo Scientific Peer Reviewed Journal, 2023)
The article describes ways to improve product policy at domestic enterprises in an innovative economy.